Embossed Mie resonator arrays composed of compacted TiO(2) nanoparticles for broadband anti-reflection in solar cells - Visser, Dennis (Sci Rep, 2020)
Mie resonator arrays formed by embossing titanium dioxide (TiO(2)) nanoparticles (NPs) from solution are investigated as optical coatings for anti-reflection applications. Compacted nanoparticle assemblies offer unique possibilities to tailor the effective refractive index (RI). Here, we demonstrate a simple table-top, low pressure, and low temperature method to fabricate structured optical coatings. TiO(2) nanostructures in the form of nanodisks support Mie resonances in the visible wavelength spectrum and exhibit strong forward scattering into the high index substrates, making them suitable as broadband anti-reflection coatings for solar cells. TiO(2) NP-based nanodisk arrays are designed, fabricated, and characterized regarding their anti-reflection properties on Si, GaAs, and InP substrates and solar cells. Detailed finite-difference time-domain simulations are performed to optimize the TiO(2) NP-based Mie resonator arrays for the broadband anti-reflection as well as to explain the measured reflectance spectra. The solar-weighted reflectance is used as a figure of merit (FoM). TiO(2) nanodisk arrays on Si show a FoM of ~ 7% in the 400–1,100 nm wavelength spectrum; similar values are obtained for GaAs and InP substrates. TiO(2) nanodisk arrays embossed directly on prefabricated planar single-junction Si, GaAs, and InP solar cells result in an appreciable increase (~ 1.3 times) in the short-circuit current densities.